Covid rehabilitation in two Malaysian Tertiary Hospitals - Abu Hassan, Salmah Anim; Chen, Yit Ng; Zainal Abidin, Muhammad ’Adil; Mohd Rozali, Zetty Noreeta; Han, Han Sim; Mohd Azhar, Nur Syuhada (Elsevier, 2022)
Research Objectives To investigate the severity of COVID-19 infections and complications experienced during inpatient admission.